Arabidopsis Phospholipase C3 is Involved in Lateral Root Initiation and ABA Responses in Seed Germination and Stomatal Closure. (22nd December 2017) - Zhang, Qianqian; van Wijk, Ringo; Shahbaz, Muhammad; Roels, Wendy; Schooten, Bas van; Vermeer, Joop E M; Zarza, Xavier; Guardia, Aisha; Scuffi, Denise; Garca-Mata, Carlos; Laha, Debabrata; Williams, Phoebe; et al.
Abstract: Phospholipase C (PLC) is well known for its role in animal signaling, where it generates the second messengers, inositol 1, 4, 5-trisphosphate (IP3 ) and diacylglycerol (DAG), by hydrolyzing the minor phospholipid, phosphatidylinositol 4, 5-bisphosphate (PIP2 ), upon receptor stimulation. In plants, PLC's role is still unclear, especially because the primary targets of both second messengers are lacking, i.e. the ligand-gated Ca 2+ channel and protein kinase C, and because PIP2 levels are extremely low. Nonetheless, the Arabidopsis genome encodes nine PLCs. We used a reversed-genetic approach to explore PLC's function in Arabidopsis, and report here that PLC3 is required for proper root development, seed germination and stomatal opening. Two independent knock-down mutants, plc3-2 and plc3-3, were found to exhibit reduced lateral root densities by 10–20%. Mutant seeds germinated more slowly but were less sensitive to ABA to prevent germination. Guard cells of plc3 were also compromised in ABA-dependent stomatal closure. Promoter–β-glucuronidase (GUS) analyses confirmed PLC3 expression in guard cells and germinating seeds, and revealed that the majority is expressed in vascular tissue, most probably phloem companion cells, in roots, leaves and flowers. In vivo 32 Pi labeling revealed that ABA stimulated the formation of PIP2 in germinating seeds and guard cell-enriched leaf peels, which was significantly reduced in plc3 mutants. Overexpression of PLC3 had no effect on root system architecture or seed germination, but increased the plant's tolerance to drought. Our results provide genetic evidence for PLC's involvement in plant development and ABA signaling, and confirm earlier observations that overexpression increases drought tolerance. Potential molecular mechanisms for the above observations are discussed.